Intersection Cultural Value, Nationalism, and Commodification behind the Garuda Chair as Jepara’s Signature Industries - Ade Ariyani Sari Fajarwati; Octaviana Sylvia Caroline; Laura Andina Wulandari (Bina Nusantara University, 2020)
The aims of the research were to identify the cultural value and nationalism behind the Garuda chair and to compare it with another style that had more sellable value as commodities. The research used a qualitative descriptive methodology using literature, observation, site visit, and interview data to be analyzed. In conclusion, the Garuda chair has a potential to become an Indonesian commodity in the furniture market and international community by promoting the cultural value behind it and the effectiveness of material using for the chair.